Road safety awareness and practices among university students - Upadhyay, Rajan; Beng, Ashutosh Johnson; Prakash, Aman; Anjali (International Journal Of Community Medicine And Public Health, 2026)
Background: Road traffic accidents (RTAs) remain a major cause of preventable death and disability worldwide particularly among young adults aged 15 to 29 years. University students are especially vulnerable because of frequent vehicle use and greater engagement in risk taking behaviours. This study assessed road safety-reported practices among university students in Lucknow, India, and examined differences by gender and year of study. Methods: A descriptive cross-sectional study was conducted among 308 students at the University of Lucknow between January and May 2026 using a pre tested, self- administered questionnaire. Participation was voluntary, and informed consent was obtained from all participants before data collection. Awareness and practice scores were analysed using independent samples t tests and one way ANOVA, with statistical significance set at p<0.05. Results: The study included 200 males (65%) and 108 females (35%), with mean ages of 21.05 and 22.21 years, respectively. Most participants correctly identified zebra crossings, Knowledge of helmet regulations was poor and less than half of the participants possessed a valid driving license, and a notable proportion reported driving after consuming alcohol. No significant differences in awareness or practice scores were observed by gender or year of study (p>0.05). Conclusions: University students demonstrated moderate road safety awareness, but substantial gaps remained between knowledge and safe practices, particularly regarding helmet use, licensing, and drink driving, Curriculum integrated road safety education, stricter enforcement, and licensing initiatives are needed to promote safe driving behaviours.